The clinicopathological and immunohistochemical features of breast carcinomas with signet-ring-cell differentiation - Jie Zheng; Junlin Liu; Wan Yang; Jia Yao; Jiao Guo; Changqing Liu (World Journal of Surgical Oncology, 2023)
Abstract Background This study investigated the clinicopathological features, immunophenotypic characteristics and differential diagnosis of primary breast carcinomas with signet ring cell differentiation, as well as differences in the traits of signet ring-like cell mucin. Methods A total of five cases of primary breast cancer diagnosed with signet ring cell differentiation and treated at The First People’s Hospital of Jingmen from January 2016 to December 2021 were collected. HE, immunohistochemical staining, and AB-PAS staining were used for the analysis. Results Although we strictly selected all the primary breast cancer cases with signet ring cell differentiation, there were differences in the arrangement of the cells and the grading of nuclei. Our immunohistochemical results showed that the ER was consistently strongly positive, and the PR expression was not consistent, while all the cases of HER2 were negative. CK7 was negative in one case, and CK20 and CK5/6 were not expressed in all the cases. The mucin MUC1 was positive and showed two patterns. MUC2 was strongly positive in all the cases. All the cases were negative for CDX2, SATB2, PAX8, TTF-1, and Napsin A, while the positive expression of COX2, Villin, and WT-1 was not constant. One case expressed neuroendocrine markers. The expression level of Ki67 was between 10 and 30%. AB (pH 2.5)-PAS staining revealed that the intracellular mucus contained more cells with neutral mucus, while the extracellular mucus was mainly acidic. Conclusion We found that histological morphology, cell morphology, and nuclear grading differentiate among different cases. The immunohistochemical characteristics of primary breast cancers diagnosed with signet ring cell differentiation are helpful for identification. The differences in the expression patterns of mucins may be related to unfavorable clinicopathological factors, but their usefulness as a prognostic marker remains to be further understood. The heterogeneity of cell mucus, the differentiation of tumor cells, and the phenotypic changes of tumors also need further study.